Análisis y evaluación de las vulnerabilidades y riesgos asociados con las cookies de inicio de sesión y de terceros en sitios web - Chávez Vergara, Luis Daniel (2023)
In this case study on the analysis and assessment of vulnerabilities and risks related to login and third-party cookies on websites, common vulnerabilities and significant risks were identified. Through quantitative and qualitative research, common vulnerabilities were identified, highlighting the threats of man-in-the-middle attacks and session hijacking. Controlled penetration and experiment tests confirmed the possibility of cookie-related attacks. As a result, solid strategies were proposed to mitigate and prevent these risks, emphasizing the importance of user education and balance in the implementation of solutions. This study contributes to improving online security and protecting users' privacy in the digital environment